Effects of intensive exercise training on immunity in athletes - Pyne, D. B.; Gleeson, M. (International Journal of Sports Medicine, 1998)
A large number of studies have failed to show whether exercise-induced perturbations in immune function are associated with the incidence of infection. "Sports immunology", examining the interaction of physical, psychological and environmental stress on immunity, is emerging as a sub-discipline of sports medicine. A series of studies by our research team has profiled the immune responses of elite swimmers during training. Serum immunoglobulin and IgG subclass levels were lower in swimmers than controls. Suppression of mucosal immune parameters has been associated with the risk of upper respiratory tract infection. Swimmers with a lower pre-season salivary IgA and/or lower pre-exercise salivary IgA level were more likely to contract an URTI during a 7-month training period. In a shorter 12-week study, infected swimmers had a mean salivary IgM concentration that dropped more sharply after a single training session. Significant declines in natural killer cell count and neutrophil oxidative activity were not associated with URTI. Despite systemic and mucosal immunosuppression a cohort of swimmers were also able to mount an antibody response to pneumococcal vaccine equivalent to that of sedentary individuals. Observations of chronic suppression of aspects of host defence and the significant relationship between changes in mucosal immune parameters and URTI, provide a framework for assessment of the immune status of athletes. The underlying causes of upper respiratory tract distress symptoms may be infective, inflammatory or allergic in origin: a differential diagnosis has implications for treatment and management.